1992
DOI: 10.1128/jb.174.5.1619-1625.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of the muramidase-2 gene from Enterococcus hirae

Abstract: Extracellular muramidase-2 of Enterococcus hirae ATCC 9790 was purified to homogeneity by substrate binding, guanidine-HCI extraction, and reversed-phase chromatography. A monoclonal antibody, 2F8, which specifically recognizes muramidase-2, was used to screen a genomic library of E. hirae ATCC 9790 DNA in bacteriophage Agtll. A positive phage clone containing a 4.5-kb DNA insert was isolated and analyzed. The EcoRI-digested 4.5-kb fragment was cut into 2.3-, 1.0-, and 1.5-kb pieces by using restriction enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…These data indicate that the protein, immunoreactivity, and enzymatic activity of extracellular M-2 are stable when it is incubated under these conditions. Consequently, proteinase inhibitors were not used in further experiments (e.g., purification to homogeneity of extracellular M-2 [3]). …”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that the protein, immunoreactivity, and enzymatic activity of extracellular M-2 are stable when it is incubated under these conditions. Consequently, proteinase inhibitors were not used in further experiments (e.g., purification to homogeneity of extracellular M-2 [3]). …”
Section: Resultsmentioning
confidence: 99%
“…The Ami protein is predicted to have a two-domain structure. The presence of two domains (a catalytic domain and a non-catalytic, cell-wall-binding domain) appears to be a common feature of autolysins (Chu et al, 1992;Kuroda et al, 1992;Romero et al, 1990). The high homology (49% identity over 183 aa) of the N-terminal domain of Ami to the amidase domain of the S. aureus autolysin At1 (Foster, 1995, Oshida et al, 1995, suggests that Ami also has amidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…3). Such amino acid repetitions have often been observed in the noncatalytic domains of several cell wall hydrolases (4,24,27,39). We have previously reported that the N-terminal to central region of the CwlM protein is a catalytic domain and that the C-terminal repetition may be involved in its substrate specificity, i.e., the CwlM protein hydrolyzes the Micrococcus cell wall preparation more efficiently than those of B. licheniformis and B. subtilis, but the truncated CwlM protein (lacking the C-terminal repetition) has lost this preference (27).…”
Section: Cw1bmentioning
confidence: 99%